Self-cleaning superhydrophobic surfaces with underwater superaerophobicity. (15th June 2016) - George, Jijo Easo; Rodrigues, Vanessa R.M.; Mathur, Deepak; Chidangil, Santhosh; George, Sajan D.
Abstract: Nature-inspired engineering of roughness of the surfaces at micro and nano-length scales offers possibilities of tailoring materials for diverse applications including self-cleaning surfaces, droplet transportation, cell adhesion and oil-water separation. Recent efforts have begun to focus on employing femtosecond-long laser pulses to create such dual length scale roughness at the surface of different kinds of materials including metals, semiconductors and polymers. Herein, we report the fabrication of polymer surfaces that exhibit simultaneous superhydrophobicity and underwater superaerophobicity by replicating femtosecond laser fabricated patterns via soft lithography. Further, by tailoring a single parameter-the laser fluence-we demonstrate tunability of material parameters like anisotropy in wetting, contact angle hysteresis, work of adhesion, and droplet (air bubble) splitting (transport) of the replicated structures. We confirm, using micro-Raman spectroscopy and atomic force microscopy, that our laser patterning does not induce any chemical modification on the polymer but only induces physical modifications-changes in surface roughness-are responsible for the observed tailoring capability. We believe that the replication route provides a cost-effective and green approach to fabricate surfaces with superhydrophobicity and underwater superaerophobicity. Such surfaces can have enormous potential applications in microfluidic devices, droplet manipulation, and energy conversion and storage. Graphical abstract: Highlights: Increase in hydrophobicity and aerophobicity of polymethylmethacrylate with femtosecond laser patterning. Replicated laser patterns on polymethylmethacryalte exhibit superhydrophobicity and superaerophobicity. Periodicity of the laser patterns also influence the water droplet and air bubble behavior onto the substrates.